Safety and Efficacy of Bivalirudin versus Unfractionated Heparin Monotherapy in Patients with CAD and DM Undergoing PCI: A Retrospective Observational Study - Jing Li; Sanbao Chen; Sicong Ma; Mingque Yang; Zizhao Qi; Kun Na; Miaohan Qiu; Yi Li; Yaling Han (Cardiovascular Therapeutics)
Introduction. Optimal anticoagulants for patients with diabetes mellitus (DM) undergoing percutaneous coronary intervention (PCI) are unclear. This retrospective observational study is aimed at evaluating efficacy and safety of bivalirudin versus unfractionated heparin (UFH) monotherapy in patients with DM undergoing PCI. Methods. A total of 3890 diabetic patients receiving PCI in the General Hospital of Northern Theater Command were divided into the bivalirudin group (n=869) and the UFH group (n=3021) according to different anticoagulant therapy regimens. Indication for PCI was in accordance with current guidelines including national cardiovascular data registry. The primary endpoint was 30-day net adverse clinical events (NACEs). The secondary endpoints included 30-day major adverse cardiac and cerebral events (MACCEs), bleeding events defined according to the Bleeding Academic Research Consortium (BARC) definition, and stent thrombosis (ST). Patients were matched by propensity score at a ratio of 1 : 1. Results. After propensity score matching, the bivalirudin group was associated with a lower incidence of NACEs (3.0% vs. 6.0%, P=0.003) than the UFH group. The incidence of MACCE (1.7% vs. 3.3%, P=0.033) was significantly lower in the bivalirudin group, mainly due to a lower mortality rate (0.6% vs. 2.0%, P=0.010). In addition, patients in the bivalirudin group had less bleeding (1.4% vs. 3.0%, P=0.022) than those in the UFH group, although BARC 2, 3, and 5 bleeding (0.1% vs. 0.6%, P=0.218) was numerically lower. Conclusion. In diabetic patients undergoing PCI, bivalirudin was significantly associated with reduced risks of 30-day NACE and MACCE, mainly driven by the lower rates of bleeding and mortality, compared with heparin monotherapy.